Berpikir Kreatif dan analisis Peserta Didik Melalui Model Pembelajaran Problem Posing ditinjau dari Skimming and Mind Mapping Gelombang Mekanik - Febriani, Marosyana Ayu; Ellianawati, Ellianawati; Wahyuni, Siti; Nurbaiti, Upik (UPEJ Unnes Physics Education Journal, 2021)
Creative and analyzing thingking is a competence that students need in studying physics on the subject of mechanical waves by developing ideas with the result that they can be analyzed through examples of everyday life. The competence of creative thinking and analyzing of class XI students in SMA Negeri 1 Dempet, Demak Regency when studying physics is less optimal and feels bored faster. This is because students still depend on the formulas used without knowing the concept, and they are passive in participating in learning activities by only paying attention to the teacher's explanation. Learning that is suitable for developing creative thinking and analytical skills is to use the Problem Posing learning model in terms of skimming and mind mapping, with the aim of research to determine the effectiveness and describe the competence to think creatively and analyze. This study used a mixed methods and the sample was selected through purposive sampling technique so that the experimental class and control class were obtained. In the experimental class, the treatment was given to the Problem Posing learning model in terms of skimming and mind mapping, while the control class was given treatment of the Problem Based Learning learning model. The results showed that the more students follow the learning using Problem Posing through skimming and mind mapping techniques, the better the final competence test results for creative thinking and analyzing. This is shown based on triangulation in each category of skimming and mind mapping observations with the final ability of creative thinking and analysis